Some Fixed Point Theorems for Generalized \(α\)-Admissible \(Z\)-Contraction via Simulation Function - Shriwas, Manoj Kumar; Dubey, Anil Kumar; Mishra, Urmila (Communications in Mathematics and Applications, 2024)
In this paper, we prove some fixed point theorems in metric-like space by using generalized \(α\)-admissible mapping embedded in the simulation function. Our results generalize and extend several known results on literature.